PENDIDIKAN ANAK DALAM KELUARGA PADA MASA COVID-19: PENDIDIKAN ANAK DALAM KELUARGA PADA MASA COVID-19 - Herosa Putri Herosa Putri (Prodi PIAUD, Fakultas Tarbiyah dan Keguruan, UIN Sulthan Thaha Saifuddin Jambi, 2021)
This journal aims to find out how parents educate their children at home during Covid-19. Some of the results of research from various journals stated that the influence of Covid-19 on all people in this world, one of which is Indonesia. The government applies so that the family is good, father, mother and child to remain at home and keep a distance, and wear a mask outside the house. With the existence of Covid-19 all offices, schools, buildings, while closed while and will be open again when his condition has improved again. Because the school was closed by children taught by his parents at home.